ENTREPRENEURIAL BEHAVIOUR AMONG UNDERGRADUATE BUSINESS, SOCIAL AND ENGINEERING STUDENTS: A CASE STUDY OF A PRIVATE INDONESIAN UNIVERSITY - Anggraeni Permatasari (Jurnal Manajemen Indonesia, 2018)
Most universities or higher education institutions in Indonesia are developing an effective program supporting their students to become entrepreneurs. They believe that entrepreneurial behaviour can be developed through entrepreneurship education. Therefore, these universities continually improve their entrepreneurship curriculum by integrating theoretical entrepreneurship concepts and practical contexts within such education. The purpose of the research reported here is to compare the effects of personality trait dimensions on student’s entrepreneurial ambitions and their behavior. The study used personality trait dimensions such as internal locus of control, need for achievement, risk tolerance and entrepreneurial awareness as independent variables. Quantitative methods, including Structural Equation Modelling (SEM), were applied for the purposes of data analysis. The research populations consisted of final year undergraduate students who had already undergone an entrepreneurship learning program in Indonesia. Data collection employed questionnaires distributed to undergraduate students drawn from three different faculties: Business Studies, Social Studies and Engineering, within private universities. The measurement instrument consisted of a Likert scale 1-7. The results demonstrated that private university-sector entrepreneurial education, by enhancing certain personality traits, has significant effects on the entrepreneurial behavior of students. The research findings can be used to monitor and evaluate the entrepreneurial learning process within higher education. The implications can be used for policy makers and educators to add value at the design stage of entrepreneurship course syllabi within higher education institutions.